State ownership effect on firms’ FDI ownership decisions under institutional pressure: A study of Chinese outward-investing firms - Cui, L.; Jiang, Fuming (Springer, 2017)
This study incorporates political perspective into the institutional theory and investigates how state ownership interacts with firms’ home and host country institutions affecting entry mode decision of Chinese multinational enterprises.